High-strength high-thermal-conductivity micro-nano composite aramid insulation paper, preparation method and application

CN122899081APending Publication Date: 2026-10-13SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611285080.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

ANF自组装纸可形成致密三维网络,具备高拉伸强度与优异介电强度,但其致命缺陷在于:纳米纤维间氢键作用过强、网络节点完全固化,几乎无法通过纤维滑移与网络重排耗散能量,导致撕裂强度极低,微小缺陷即可引发灾难性脆性断裂,在实际绕线与装配过程中极易破损,难以单独应用于工程场景

Benefits of technology

本发明引入聚多巴胺改性与二维导热填料,构建了“钢筋-砖块-混凝土”三维网络;聚多巴胺作为仿生“胶水”,实现了对位芳纶纤维ANF、导热填料和间位芳纶PMIA纤维界面的化学键合与强物理共轭。从根本上改变了单纯物理组装易剥离的缺陷,通过纤维滑移与高能键断裂高效损耗撕裂能,使得复合绝缘纸在引入高填量无机填料后仍保持高达1500~1900 mN的撕裂强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122899081A_ABST
    Figure CN122899081A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of insulating materials, and discloses a high-strength and high-thermal-conductivity micro-nano composite aramid insulating paper, a preparation method and application, and comprises the following steps: step 1: dopamine monomers and two-dimensional thermal-conductivity nano fillers are added into an alkaline buffer solution, and a para-aramid fiber dispersion solution is added; the reaction is fully stirred to obtain a composite suspension; step 2: the composite suspension is added into a meta-aramid chopped fiber dispersion solution, and the reaction is fully stirred to obtain a core-shell structure slurry; and step 3: the core-shell structure slurry is used to prepare the required composite aramid insulating paper; the insulating paper obtained by the application has high strength and toughness, high thermal conductivity and excellent electrical insulation performance, and can be used in high-load insulation and heat dissipation scenes such as extra-high voltage transformers, new energy automobile drive motors, aerospace electrical systems and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrical insulation materials technology, specifically to a high-strength, high-thermal-conductivity micro-nano composite aramid insulating paper, its preparation method, and its application. Background Technology

[0002] With the rapid development of ultra-high voltage power transmission and transformation, new energy vehicle drive motors, aerospace electrical systems, and high-end precision electronic equipment towards high frequency, high voltage, miniaturization, and long lifespan, insulating materials, as the core foundation for the safe operation of electrical systems, must maintain excellent mechanical strength, electrical insulation performance, and environmental stability under extreme conditions such as high temperature, low temperature, strong corrosion, mechanical vibration, and high electric field coupling. Traditional insulating materials can no longer meet the comprehensive performance requirements of next-generation equipment for high breakdown field strength, high tear toughness, high temperature resistance, and aging resistance. Developing new paper-based insulating materials that combine high strength, high toughness, and high insulation reliability has become the key to breaking through the performance bottleneck of high-end electrical equipment.

[0003] Aramid insulating paper, with its rigid molecular chain and strong hydrogen bonding of aromatic polyamide, possesses excellent heat resistance, mechanical strength, and insulation properties. It is a core insulating material for equipment such as transformers, traction motors, and special cables, and is widely used in key fields such as power, transportation, and aerospace. Currently, commercially available aramid insulating paper is represented by meta-aramid nanofiber (PMIA) paper, which is typically produced using a wet papermaking process. It is made from short aramid fibers and precipitated aramid fibers. While it meets the requirements under normal operating conditions, its inherent defects become increasingly prominent under high pressure, high mechanical stress, and extreme environments. On the one hand, PMIA fibers have a chemically inert, smooth surface with few active groups, resulting in weak interfacial bonding and low lap joint strength. After forming the paper, its internal structure is loose and porous, with high porosity and uneven pore size distribution. This not only leads to low overall mechanical properties but also makes it more susceptible to partial discharge, corona discharge, and electric field distortion, accelerating insulation aging and breakdown failure. On the other hand, traditional PMIA paper struggles to balance tensile and tear strength. Microcracks easily form during coil winding and assembly, and rapid crack propagation can lead to structural tearing, severely limiting its reliability under complex mechanical conditions. Aramid nanofibers (ANFs), with their nanoscale effects, high aspect ratio, high crystallinity, and abundant surface functional groups, have become a research hotspot for high-performance insulating paper. ANF ​​self-assembled paper can form a dense three-dimensional network with high tensile strength and excellent dielectric strength, but its fatal flaw is that the hydrogen bonding between nanofibers is too strong and the network nodes are completely solidified. It is almost impossible to dissipate energy through fiber slippage and network rearrangement, resulting in extremely low tear strength. Even tiny defects can cause catastrophic brittle fracture. It is very easy to break during actual winding and assembly, making it difficult to apply alone in engineering scenarios.

[0004] Existing aramid insulating papers suffer from an irreconcilable core contradiction: traditional PMIA paper has a loose structure and insufficient mechanical and dielectric properties; pure ANF paper has excellent tensile and dielectric properties, but extremely poor tear toughness and is prone to brittle fracture. Neither can simultaneously meet the synergistic requirements of high-end electrical equipment for high tear strength, high dielectric strength, excellent thermal stability, and environmental tolerance. Under extreme temperatures, strong corrosion, and long-term high-voltage conditions, performance degrades significantly, limiting service life. Summary of the Invention

[0005] This invention addresses the problems existing in the prior art by providing a high-strength, high-thermal-conductivity micro-nano composite aramid insulating paper, its preparation method, and its application.

[0006] The technical solution adopted in this invention is: a method for preparing high-strength, high-thermal-conductivity micro / nano composite aramid insulating paper, comprising the following steps: Step 1: Add dopamine monomer and two-dimensional thermally conductive nanofiller to alkaline buffer solution, and add para-aramid fiber dispersion; stir the reaction thoroughly to obtain composite suspension; wherein, the mass ratio of dopamine monomer to two-dimensional thermally conductive nanofiller is 1-5:10-30; Step 2: Add the composite suspension obtained in Step 1 to the meta-aramid chopped fiber dispersion and stir thoroughly to obtain a core-shell structure slurry; wherein the mass ratio of para-aramid fiber to meta-aramid chopped fiber is 8-12:4-7. Step 3: The core-shell structure slurry obtained in Step 2 is used to prepare the desired composite aramid insulating paper.

[0007] Furthermore, in step 1, the two-dimensional thermally conductive nanofiller is one or both of hydroxylated hexagonal boron nitride nanosheets and alumina nanosheets.

[0008] Furthermore, in step 1, the diameter of the para-aramid fiber ranges from 8 to 12 nm, and the length ranges from 4 to 10 μm; in step 2, the diameter of the meta-aramid chopped fiber ranges from 5 to 8 nm, and the length ranges from 8 to 12 μm.

[0009] Furthermore, in step 1, the para-aramid fibers are first deprotonated and stripped; the alkaline buffer solution has a pH of 8.5.

[0010] Furthermore, in step 2, the stirring speed is 800–1000 rpm.

[0011] Furthermore, in step 3, the core-shell slurry is washed, vacuum filtered and shaped to obtain a wet paper blank; the wet paper blank is then cold-pressed, dried and hot-pressed to obtain the desired composite aramid insulating paper.

[0012] Furthermore, the pressure during the cold pressing process is 0.3–0.5 MPa, and the pressing time is 4–6 min; the hot pressing temperature is 230–250 ℃, the pressure is 12–18 MPa, and the pressing time is 4–6 min.

[0013] A high-strength, high-thermal-conductivity micro-nano composite aramid insulating paper, wherein the composite aramid insulating paper is mainly composed of meta-aramid short-cut fibers, and the surface of the main body is covered with a thermally conductive shell network. The thermally conductive shell network includes para-aramid fibers and two-dimensional thermally conductive nanofillers. The surface of the para-aramid fibers is coated with polydopamine, and the two-dimensional thermally conductive nanofillers are anchored to the surface of the para-aramid fibers by polydopamine.

[0014] Furthermore, the composite aramid insulating paper has a thickness of 45–55 μm and a density of 0.75–0.85 g / cm³.

[0015] An application of a high-strength, high-thermal-conductivity micro / nano composite aramid insulating paper, wherein the composite aramid insulating paper is used for insulating components of electronic devices.

[0016] The beneficial effects of this invention are: This invention introduces polydopamine modification and two-dimensional thermally conductive fillers to construct a three-dimensional "steel-brick-concrete" network. Polydopamine acts as a biomimetic "glue," achieving chemical bonding and strong physical conjugation at the interfaces of para-aramid fibers (ANF), thermally conductive fillers, and meta-aramid fibers (PMIA). This fundamentally overcomes the easy peeling defects of simple physical assembly. Through fiber slippage and high-energy bond breaking, it efficiently dissipates tear energy, enabling the composite insulating paper to maintain a tear strength of 1500–1900 mN even after introducing a high amount of inorganic fillers.

[0017] The composite insulating paper obtained by this invention breaks through the bottleneck of the mutual constraint between high dielectric strength and high thermal conductivity. Polydopamine-modified para-aramid fiber (ANF) and two-dimensional thermally conductive filler are in situ wrapped around meta-aramid fiber (PMIA), eliminating interfacial micropores and interfacial thermal resistance. This creates a continuous and efficient phonon heat transfer channel inside the insulating paper, resulting in an in-plane thermal conductivity of over 0.8 W / (m·K). The highly dense shell suppresses electric field distortion and space charge migration, while maintaining a high dielectric strength of 75–85 kV / mm, effectively solving the problem of heat accumulation in high-load ultra-high voltage and new power equipment.

[0018] The preparation method of this invention employs a dopamine oxidative self-polymerization reaction to drive the self-assembly of the shell material on the surface of the meta-aramid PMIA core layer, solving the problem in existing technologies where a core-shell structure cannot be obtained due to a lack of bonding force. Through wet in-situ composite molding, the interlayer bonding is tight and defect-free, balancing high performance and economy, making it suitable for high-end electrical insulation and heat dissipation applications such as ultra-high voltage transformers, new energy vehicles, and aerospace. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the composite aramid insulating paper structure obtained by the present invention.

[0020] Figure 2 This is a schematic diagram showing the surface thermal conductivity of the insulating paper obtained in Embodiment 1 and Comparative Examples 1 and 2 of the present invention.

[0021] Figure 3 This is a schematic diagram of the tensile strength mechanical properties of the insulating paper obtained in Embodiment 1 and Comparative Examples 1 and 2 of the present invention.

[0022] Figure 4 This is a schematic diagram of the tear strength mechanical properties of the insulating paper obtained in Embodiment 2 and Comparative Examples 1 and 2 of the present invention.

[0023] Figure 5 This is a schematic diagram showing the dielectric strength of the insulating paper obtained in Embodiment 2 and Comparative Examples 1 and 2 of the present invention.

[0024] In the figure: 1-PMIA fiber layer, 2-ANF aramid nanofiber, 3-PDA ​​crosslinked network, 4-two-dimensional thermally conductive nanofiller. Detailed Implementation

[0025] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.

[0026] A method for preparing a high-strength, high-thermal-conductivity micro / nano composite aramid insulating paper includes the following steps: Step 1: Add dopamine monomer and two-dimensional thermally conductive nanofiller to alkaline buffer solution, and add para-aramid fiber dispersion; stir the reaction thoroughly to obtain composite suspension; wherein, the mass ratio of dopamine monomer to two-dimensional thermally conductive nanofiller is 1-5:10-30; The two-dimensional thermally conductive nanofiller is one or both of hydroxylated hexagonal boron nitride nanosheets and alumina nanosheets. The diameter of the para-aramid fiber ranges from 8 to 12 nm, and the length ranges from 4 to 10 μm; the diameter of the meta-aramid chopped fiber in step 2 ranges from 5 to 8 nm, and the length ranges from 8 to 12 μm.

[0027] The para-aramid fibers were first subjected to deprotonation exfoliation. Poly(p-phenylene terephthalamide) (PPTA), DMSO, deionized water, and KOH were mixed in a certain proportion and stirred at room temperature for 3–5 h to achieve deprotonation exfoliation.

[0028] The specific process is as follows: A dispersion was obtained by adding a two-dimensional thermally conductive nanofiller to a Tris-HCl buffer solution with a pH of 8.5. The dispersion was then ultrasonically dispersed for 1–2 h. Dopamine hydrochloride solution was added, followed by the purified ANF dispersion. The mixture was stirred continuously at room temperature for 12–24 h. Under weakly alkaline conditions, the dopamine monomer underwent oxidative self-polymerization to form PDA. Utilizing the abundant catechol groups in PDA, strong hydrogen bonds and π-π conjugated interactions were formed between PDA and the two-dimensional thermally conductive nanofiller, ANF, and PMIA fibers, eliminating interfacial thermal resistance and achieving in-situ seamless bonding. This resulted in dopamine self-polymerization coating the ANF surface and anchoring the thermally conductive filler, yielding a PDA-modified ANF / two-dimensional thermally conductive filler composite suspension.

[0029] Step 2: Add the composite suspension obtained in Step 1 to the meta-aramid chopped fiber dispersion at a stirring speed of 800-1000 rpm, and stir thoroughly to obtain a core-shell structured slurry; wherein the mass ratio of para-aramid fiber to meta-aramid chopped fiber is 8-12:4-7; through the interfacial adhesion of PDA, a core-shell structured slurry with PMIA as the main body and a thermally conductive network as the shell is formed in situ.

[0030] Step 3: The core-shell structure slurry obtained in Step 2 is used to prepare the desired composite aramid insulating paper.

[0031] The core-shell slurry is washed, vacuum filtered, and formed into a wet paper blank. The wet paper blank is then cold-pressed, dried, and hot-pressed to obtain the desired composite aramid insulating paper. The pressure during cold pressing is 0.3–0.5 MPa, and the pressing time is 4–6 min. The hot pressing temperature is 230–250 ℃, the pressure is 12–18 MPa, and the pressing time is 4–6 min.

[0032] The oven-dry mass fraction of each component in the composite aramid insulating paper is as follows: meta-aramid short chopped fiber PMIA: 20-35%, aramid nanofiber ANF: 40-60%, two-dimensional thermally conductive nanofiller: 10-30%, polydopamine PDA: 1-5%.

[0033] Composite aramid insulating paper structure such as Figure 1As shown, the composite aramid insulating paper uses meta-aramid microfibers (PMIA) as the main body, with a thermally conductive shell network covering the surface. The thermally conductive shell network includes para-aramid nanofibers (ANF) and two-dimensional thermally conductive nanofillers. A polydopamine (PDA) biomimetic adhesive layer is coated on the ANF surface. The two-dimensional thermally conductive nanofillers are anchored to the ANF surface through the PDA layer and interwoven with the PMIA microfibers. The composite aramid insulating paper uses PDA-modified ANF as the flexible "mortar," the two-dimensional thermally conductive nanofillers as the thermally conductive "bricks," and the PMIA microfibers as the supporting "steel bars," collectively constructing a "steel bar-brick-concrete" type three-dimensional composite structure with continuous phonon heat transfer channels and a core-shell coating morphology. PDA forms strong hydrogen bonds and π-π conjugation with the two-dimensional thermally conductive nanofillers, ANF, and PMIA fibers through its catechol groups, constructing a three-dimensional composite structure with PDA-modified ANF as the flexible adhesive phase, the two-dimensional thermally conductive nanofillers as the thermally conductive units, and the PMIA microfibers as the supporting framework.

[0034] The composite aramid insulating paper has a thickness of 45–55 μm, a basis weight of 38–45 g / m², and a density of 0.75–0.85 g / cm³. Its in-plane thermal conductivity is ≥0.8 W / (m·K), tear strength is 1500–1900 mN, dielectric strength is 75–85 kV / mm, and volume resistivity is ≥1.0 × 10¹⁸. 7 Ω·cm.

[0035] Example 1 A method for preparing a high-strength, high-thermal-conductivity micro / nano composite aramid insulating paper includes the following steps: Based on oven-dry weight, the composite aramid insulating paper contains 30% PMIA microfiber, 47% ANF, 20% hydroxylated hexagonal boron nitride nanosheets, and 3% PDA; each raw material is formulated according to these weight fractions.

[0036] Step 1: The para-aramid PPTA filament fibers were uniformly cut into short fibers with a length of 6 mm using a shearing device and set aside. The PPTA fiber:DMSO:deionized water:KOH were prepared according to a mass ratio of 1:50:5:2. First, DMSO, deionized water, and KOH were added to the reaction vessel, and mechanical stirring was started until the KOH was completely dissolved, forming a homogeneous and transparent system. Then, the cut PPTA short fibers were added, and the mixture was continuously stirred at 600 rpm for 4 hours at room temperature to allow the PPTA aramid fibers to undergo sufficient deprotonation and exfoliation in the DMSO / KOH system. The final product was a stable ANF / DMSO dispersion with a deep red color, no obvious precipitation, and a significant Tyndall effect.

[0037] The obtained ANF / DMSO dispersion was subjected to solvent replacement and multiple washing with deionized water to remove residual DMSO and KOH in the system until the filtrate was nearly neutral, thus obtaining a stable aqueous ANF dispersion for later use.

[0038] Hydroxylated hexagonal boron nitride nanosheets (h-BN-OH) were weighed and added to a Tris-HCl buffer solution with a pH of 8.5. The solution was then ultrasonically dispersed for 1.5 h to obtain a uniformly dispersed h-BN-OH dispersion. During ultrasonication, the temperature of the dispersion was controlled to not exceed 35 °C to reduce agglomeration of the two-dimensional nanosheets due to localized overheating. Hydroxylated hexagonal boron nitride nanosheets exhibit high intrinsic thermal conductivity. Their surface hydroxyl groups can form hydrogen bonds with the PDA layer and the amide groups on the ANF surface, which is beneficial for improving the dispersion stability and interfacial bonding strength of the two-dimensional thermally conductive nanofiller in the aramid system.

[0039] Dopamine hydrochloride was added to the h-BN-OH dispersion and allowed to dissolve completely in a Tris-HCl buffer solution at pH 8.5. Subsequently, an aqueous ANF dispersion was slowly added to the above system, and the mixture was stirred continuously for 18 h at room temperature and in the dark to allow dopamine to undergo an oxidative self-polymerization reaction in a weakly alkaline environment, generating a PDA biomimetic adhesive layer.

[0040] On one hand, PDA is deposited and coated onto the surface of ANF to form PDA-modified ANF. On the other hand, PDA can interact with h-BN-OH nanosheets through its catechol groups, amino groups, and aromatic conjugated structures, allowing the h-BN-OH nanosheets to be stably anchored on the ANF surface, forming a PDA-ANF / h-BN composite suspension. In this composite suspension, PDA-modified ANF acts as a flexible bonding network, and h-BN-OH nanosheets act as thermally conductive functional units, together forming the thermally conductive reinforcing phase in the subsequent composite insulating paper.

[0041] Step 2: Weigh PMIA chopped fibers with an average diameter of 10 μm and a length of 6 mm. Add polyethylene oxide (PEO) as a dispersant at 0.5% of the fiber mass. Mix the PMIA chopped fibers with deionized water at a solid content of 3% to prepare a suspension. Place the mixture in a high-speed disperser and stir at 800 rpm for 30 min to ensure that the PMIA microfibers are fully dispersed without significant agglomeration or clumping, resulting in a uniformly dispersed and stable PMIA aqueous suspension.

[0042] The PDA-ANF / h-BN composite suspension obtained in step 1 was slowly and uniformly added dropwise to the PMIA aqueous suspension under high-speed stirring. The addition time was controlled at 15–20 min, and the stirring speed was maintained at 800–1000 rpm throughout the process. After the addition was completed, stirring was continued for 30 min to ensure that the PDA-modified ANF and h-BN-OH nanosheets were fully dispersed and attached to the surface and interfiber spaces of the PMIA microfibers, thus obtaining the PMIA / PDA-ANF / h-BN composite fiber slurry.

[0043] In this process, PMIA microfibers serve as the main skeleton of the paper, providing flexible support and tear resistance; PDA-modified ANF acts as a flexible binder, enhancing the interfacial bonding between PMIA microfibers and filling the interfiber pores; h-BN-OH nanosheets act as a two-dimensional thermally conductive filler, forming thermally conductive connection points and in-plane heat transfer paths within the PDA-ANF network. Subsequently, the mixed slurry is washed multiple times using a vacuum filtration device until the filtrate is nearly neutral to remove unreacted monomers, free PDA particles, and residual salts, yielding a stable composite fiber slurry that can be directly used for wet forming.

[0044] Step 3: Slowly and evenly pour the composite fiber slurry obtained in Step 2 into a vacuum papermaker, controlling the papermaking basis weight to 41 g / m². Turn on the vacuum system for filtration and shaping to obtain a wet paper blank with uniform thickness and a smooth surface. Transfer the wet paper blank to a flat vulcanizing machine and cold press it at 0.4 MPa for 5 min to remove excess free moisture and increase the initial contact area between fibers. Then, place the pre-pressed paper blank into a vacuum drying oven and vacuum dry it at 105 ℃ and 0.1 MPa for 8 min to obtain a dry aramid composite paper blank without obvious curling.

[0045] The dried aramid composite paper blank was placed in a hot press, with polytetrafluoroethylene (PTFE) release cloth placed on both the upper and lower surfaces of the blank to ensure smooth demolding. The temperature was uniformly increased to 240 °C at a rate of 10 °C / min, and then hot-pressed for 5 min at a pressure of 15 MPa. During the hot pressing process, the PMIA microfibers underwent moderate thermal softening deformation, and the fiber nodes interlocked with each other; the PDA-modified ANF network was further densified and the interfiber bonding was enhanced; the two-dimensional thermally conductive nanofiller formed a tighter overlapping contact in the in-plane direction of the paper, thereby improving the structural density, mechanical strength, and in-plane thermal conductivity of the composite paper.

[0046] After hot pressing, the paper is allowed to cool naturally to room temperature, then removed and demolded to obtain a high-strength, high-thermal-conductivity micro-nano composite aramid insulating paper with a finished thickness of approximately 50 μm.

[0047] Example 2 The preparation steps in this embodiment are the same as those in Example 1, except that, based on oven-dry weight, the composite aramid insulating paper contains 30% PMIA microfiber, 52% ANF, 15% hydroxylated hexagonal boron nitride nanosheets, and 3% PDA; each raw material is prepared according to these weight fractions.

[0048] Example 3 The preparation steps in this embodiment are the same as in Example 1, except that, based on oven-dry weight, the composite aramid insulating paper contains 25% PMIA microfiber, 46% ANF, 25% two-dimensional thermally conductive nanofiller, and 4% PDA; each raw material is prepared according to these weight fractions. The two-dimensional thermally conductive nanofiller is obtained by mixing hydroxylated hexagonal boron nitride nanosheets and alumina nanosheets in a mass ratio of 4:1.

[0049] In step 2, hydroxylated hexagonal boron nitride nanosheets and alumina nanosheets were first added to a Tris-HCl buffer solution with a pH of 8.5 and ultrasonically dispersed for 2 hours. Then, dopamine hydrochloride and ANF aqueous dispersion were added for in-situ polymerization. The compounded two-dimensional thermally conductive nanofiller can form more thermally conductive connection points inside the paper, further improving the in-plane thermal conductivity; at the same time, the PDA biomimetic adhesive layer can improve the interfacial bonding between the thermally conductive filler and the aramid fiber, avoiding a significant decrease in mechanical and insulation properties due to the increase in filler content.

[0050] Comparative Example 1 The preparation method of pure ANF aramid nanopaper includes the following steps: Step 1: The para-aramid PPTA filament fibers were uniformly cut into short fibers with a length of 6 mm using a shearing device and set aside. The PPTA fiber:DMSO:deionized water:KOH were prepared according to a mass ratio of 1:50:5:2. First, DMSO, deionized water, and KOH were added to the reaction vessel, and mechanical stirring was started until the KOH was completely dissolved, forming a homogeneous and transparent system. Then, the cut PPTA short fibers were added, and the mixture was continuously stirred at 600 rpm for 4 hours at room temperature to allow the PPTA aramid fibers to undergo sufficient deprotonation and exfoliation in the DMSO / KOH system. The final product was a stable ANF / DMSO dispersion with a deep red color, no obvious precipitation, and a significant Tyndall effect.

[0051] The obtained ANF / DMSO dispersion was subjected to solvent replacement and multiple washing with deionized water to remove residual DMSO and KOH in the system until the filtrate was nearly neutral, thus obtaining pure ANF fiber slurry that could be directly used for papermaking.

[0052] Step 2: Slowly and evenly pour the pure ANF fiber slurry obtained in Step 1 into the vacuum paper machine, control the papermaking basis weight to 41 g / m², turn on the vacuum system to filter and form, and obtain a wet paper blank with uniform thickness and smooth surface.

[0053] The wet paper blank was transferred to a flat vulcanizing machine and cold-pressed at 0.4 MPa for 5 min to remove excess free moisture and increase the initial contact area between fibers. The pre-pressed paper blank was then placed in a vacuum drying oven and vacuum-dried at 105 °C and 0.1 MPa for 8 min to obtain a dry, non-curled pure ANF paper blank.

[0054] The dried pure ANF paper blank was placed in a hot press, with polytetrafluoroethylene release cloth placed on both the top and bottom surfaces of the paper blank to ensure smooth demolding. The temperature was uniformly increased to 240 ℃ at a rate of 10 ℃ / min, and hot-pressed at a pressure of 15 MPa for 5 min. After hot pressing, the paper blank was allowed to cool naturally to room temperature, removed, and demolded to obtain pure ANF aramid nanopaper with a finished thickness of approximately 38 μm.

[0055] Comparative Example 2 The preparation method of pure PMIA aramid nanopaper includes the following steps: Step 1: Weigh PMIA short-cut fibers with an average diameter of 10 μm and a length of 6 mm, and mix them with PMIA precipitated fibers at a mass ratio of 7:3. Add polyethylene oxide (PEO) as a dispersant at 0.5% of the total fiber mass. Mix the mixed fibers with deionized water at a solid content of 3% to prepare a suspension. Place the mixture in a high-speed disperser and stir at 800 rpm for 30 min to ensure that the fibers are fully dispersed, without agglomeration or clumping, and obtain a pure PMIA fiber slurry with uniform dispersion and good stability.

[0056] Step 2: Slowly and evenly pour the pure PMIA fiber slurry obtained in Step 1 into a vacuum sheeter, controlling the sheet-forming basis weight to 41 g / m². Turn on the vacuum system for filtration and forming to obtain a wet paper blank with uniform thickness and a smooth surface. Transfer the wet paper blank to a flat vulcanizing machine and cold press it at 0.4 MPa for 5 min to remove excess free moisture. Then, place the pre-pressed paper blank into a vacuum drying oven and vacuum dry it at 105 ℃ and 0.1 MPa for 8 min to obtain a dry, non-curled pure PMIA paper blank.

[0057] The dried pure PMIA paper blank is placed in a hot press, with polytetrafluoroethylene (PTFE) release cloth placed on both the top and bottom surfaces to ensure smooth demolding. The temperature is uniformly increased to 240 °C at a rate of 10 °C / min, and then hot-pressed at 15 MPa for 5 min. After hot pressing, the paper blank is allowed to cool naturally to room temperature, removed, and demolded to obtain pure PMIA aramid insulating paper with a finished thickness of approximately 50 μm.

[0058] Comparative Example 3 The other steps in this comparative example are the same as in Example 1, except that dopamine hydrochloride is not included in step 1.

[0059] Comparative Example 4 The other steps in this comparative example are the same as those in Example 1, except that step 1 does not include two-dimensional thermally conductive nanofillers.

[0060] Figure 2 The figure shows the in-plane thermal conductivity of the aramid insulating paper obtained in Example 1, Comparative Example 1, and Comparative Example 2. As can be seen from the figure, the in-plane thermal conductivity of pure PMIA aramid insulating paper and pure ANF aramid insulating paper is relatively low, with 0.16 W / (m·K) for Comparative Example 1 and 0.15 W / (m·K) for Comparative Example 2. However, the in-plane thermal conductivity of the composite aramid insulating paper obtained in the examples is significantly improved, with an in-plane thermal conductivity of approximately 0.92 W / (m·K).

[0061] The in-plane thermal conductivity of the composite paper in Comparative Example 3 without PDA was tested to be 0.55 W / (m·K), and the in-plane thermal conductivity of the composite paper in Comparative Example 4 without two-dimensional thermally conductive nanofillers was 0.23 W / (m·K). The in-plane thermal conductivity of Examples 2 and 3 was also significantly higher than that of the comparative examples, with Example 3 reaching 1.12 W / (m·K), significantly higher than all the comparative examples. Although the in-plane thermal conductivity of Comparative Examples 3 and 4 was improved compared with pure PMIA aramid insulating paper and pure ANF aramid insulating paper, it was still significantly lower than that of the composite aramid insulating paper obtained in the examples.

[0062] PDA-modified ANF can enhance the interfacial bonding between two-dimensional thermally conductive nanofillers and aramid fibers, reduce interfacial thermal resistance, and enable two-dimensional thermally conductive nanofillers to more effectively perform in-plane heat transfer.

[0063] Figure 3 This diagram illustrates the tensile strength of the aramid insulating paper obtained in Examples 1, 1, and 2 of this invention. As can be seen from the diagram, the tensile strength of the pure ANF aramid nanopaper in Comparative Example 1 is 56.8 MPa, and the tensile strength of the pure PMIA aramid insulating paper in Comparative Example 2 is 27.8 MPa. The tensile strength of the composite insulating paper obtained in Example 1 is 60.4 MPa.

[0064] The tensile strengths of the insulating papers obtained in Comparative Examples 3 and 4 were tested to be 45.6 MPa and 58.9 MPa, respectively. It can be seen that PDA-modified ANF can enhance the interfacial bonding between PMIA microfibers and improve the interfacial defects that may be caused by the introduction of two-dimensional thermally conductive fillers, so that the composite paper can maintain high tensile strength while achieving high thermal conductivity.

[0065] Figure 4 This diagram illustrates the tear strength of aramid insulating paper obtained in Examples 1, 1, and 2 of this invention. As can be seen from the diagram, the tear strength of the pure ANF aramid nanopaper in Comparative Example 1 is 40 mN, indicating poor tear resistance; the tear strength of the pure PMIA aramid insulating paper in Comparative Example 2 is 500 mN. The tear strength of the composite aramid insulating paper obtained in Example 2 is 1760 mN.

[0066] The tear strength of the composite paper obtained in Comparative Example 3 was 1120 mN, and that of the composite paper obtained in Comparative Example 4 was 1899 mN. The tear strength of the composite aramid insulating paper obtained in Example 2 was 1850 mN. The tear strength of the composite aramid insulating paper obtained in Example 3 was 1580 mN. The test results show that even with the introduction of a certain amount of two-dimensional thermally conductive inorganic filler, the composite paper obtained in the embodiments of the present invention can still maintain high tear strength. This is because PMIA microfibers can provide energy-dissipating mechanisms such as fiber pull-out, slippage, and network rearrangement during the tearing process, while PDA-modified ANF enhances the interfacial bonding between fibers and alleviates stress concentration, thereby effectively inhibiting rapid crack propagation.

[0067] Figure 5 This diagram illustrates the dielectric strength of the aramid insulating paper obtained in Example 2, Comparative Example 1, and Comparative Example 2 of the present invention. As can be seen from the diagram, the dielectric strength of the pure ANF aramid nanopaper obtained in Comparative Example 1 is 81.5 kV / mm, while the dielectric strength of the pure PMIA aramid insulating paper in Comparative Example 2 is only 33.2 kV / mm. The dielectric strength of the composite aramid insulating paper obtained in Example 2 is 83.1 kV / mm. The volume resistivity of the insulating paper obtained in Example 2, Comparative Example 1, and Comparative Example 2 was tested to be 2.2 × 10¹⁸. 7 Ω·cm, 3.7×10¹ 7 Ω·cm, 1.1×10¹ 7 Ω·cm.

[0068] The dielectric strength of the insulating paper obtained in Comparative Example 3 was tested to be 68.5 kV / mm, and the dielectric strength of the insulating paper obtained in Comparative Example 4 was 82.8 kV / mm. The dielectric strengths of the composite insulating papers obtained in Examples 1 and 3 were 80.6 kV / mm and 76.9 kV / mm, respectively. The volume resistivity of the insulating papers obtained in Comparative Example 3, Comparative Example 4, Examples 1, and Examples 3 was 7.6 × 10¹⁸. 6 Ω·cm, 2.0×10¹ 7 Ω·cm, 1.8×10¹ 7 Ω·cm, 1.2×10¹ 7 Ω·cm.

[0069] The present invention can maintain high dielectric strength and volume resistivity after introducing two-dimensional thermally conductive filler, thus meeting the requirements for use of high voltage electrical insulation materials.

[0070] The performance test results of the insulating paper obtained in the embodiments and comparative examples of the present invention are shown in Table 1.

[0071] Table 1. Performance test results of insulating paper obtained in Examples 1-3 and Comparative Examples 1-4

[0072] The results above show that Comparative Examples 1 and 2 demonstrate that pure aramid materials (pure ANF or pure PMIA) have inherent limitations in terms of mechanical framework, dielectric strength, and thermal conductivity, making it impossible to meet practical application requirements. Comparative Example 4 proves that the "PMIA@ANF binary micro-nano interwoven network" pre-constructed in this invention can produce a significant structural synergistic enhancement effect, providing a solid matrix guarantee with extremely high tear strength and dielectric strength for subsequent inorganic fillers. Comparative Example 3 further demonstrates that if inorganic thermally conductive fillers are directly physically blended without PDA modification, it will lead to severe interfacial incompatibility, phonon heat transfer obstruction, and significant mechanical degradation, thus highlighting the irreplaceable nature of the PDA interfacial crosslinking step. Finally, the data from Examples 1 to 3 fully confirm that the insulating paper of this invention, through the structural design of "binary network matrix support + PDA interfacial crosslinking bridging + two-dimensional filler heat conduction," successfully eliminates interfacial thermal resistance, achieving a significant leap in in-plane thermal conductivity while perfectly maintaining the excellent tear strength and electrical insulation performance of the matrix, realizing a comprehensive leap in the overall performance of the material.

[0073] This invention provides a high-strength, high-thermal-conductivity micro / nano composite aramid insulating paper, with meta-aramid fiber (PMIA) as the main body, and a thermally conductive shell network covering the surface of the main body. The thermally conductive shell network is composed of aramid nanofibers (ANF) and two-dimensional thermally conductive nanofillers. The ANF surface is coated with a polydopamine (PDA) biomimetic adhesive layer. The two-dimensional thermally conductive nanofillers are uniformly anchored to the ANF surface through the PDA layer and interwoven with the PMIA microfibers. This forms a three-dimensional composite structure of "reinforcement-brick-concrete" type, with PDA-modified ANF as the flexible "mortar," two-dimensional thermally conductive nanofillers as the thermally conductive "bricks," and PMIA microfibers as the supporting "steel bars," possessing continuous phonon heat transfer channels and a core-shell coating morphology. This achieves chemical bonding and strong physical conjugation at the interface of ANF, thermally conductive fillers, and PMIA fibers. This unique modification mechanism fundamentally overcomes the inherent weakness of simple physical assembly, which is prone to peeling. It efficiently dissipates tear energy through fiber slippage and high-energy bond breaking, allowing the composite insulation paper to maintain a tear strength of 1500–1900 mN even after the introduction of a large amount of inorganic filler. PDA-modified ANF and two-dimensional thermally conductive filler are in-situ wrapped around the PMIA, completely eliminating interfacial micropores and interfacial thermal resistance. This successfully constructs a continuous and efficient phonon heat transfer channel within the insulation paper, causing the in-plane thermal conductivity to jump to over 0.8 W / (m·K). Simultaneously, the highly dense shell suppresses electric field distortion and space charge migration, maintaining a high dielectric strength of 75–85 kV / mm, effectively addressing the heat accumulation problem in high-load ultra-high voltage and new power equipment.

[0074] The composite aramid insulating paper obtained by this invention possesses high strength and toughness, high thermal conductivity, and excellent electrical insulation properties. It also exhibits superior high-temperature resistance, cryogenic resistance, acid, alkali, and salt resistance, hydrophobicity, antifouling properties, and self-extinguishing characteristics. Its performance retention rate is high under extreme environments and corrosive conditions ranging from -196 ℃ to 200 ℃, and its long-term service stability is far superior to traditional aramid paper. It is suitable for high-end electrical insulation and heat dissipation applications such as ultra-high voltage transformers, new energy vehicles, and aerospace.

Claims

1. A method for preparing a high-strength, high-thermal-conductivity micro / nano composite aramid insulating paper, characterized in that, Includes the following steps: Step 1: Add dopamine monomer and two-dimensional thermally conductive nanofiller to alkaline buffer solution, and add para-aramid fiber dispersion; The reaction was thoroughly stirred to obtain a composite suspension; wherein the mass ratio of dopamine monomer to two-dimensional thermally conductive nanofiller was 1-5:10-30. Step 2: Add the composite suspension obtained in Step 1 to the meta-aramid chopped fiber dispersion and stir thoroughly to obtain a core-shell structure slurry; wherein the mass ratio of para-aramid fiber to meta-aramid chopped fiber is 8-12:4-7. Step 3: The core-shell structure slurry obtained in Step 2 is used to prepare the desired composite aramid insulating paper.

2. The method for preparing a high-strength, high-thermal-conductivity micro / nano composite aramid insulating paper according to claim 1, characterized in that, In step 1, the two-dimensional thermally conductive nanofiller is one or both of hydroxylated hexagonal boron nitride nanosheets and alumina nanosheets.

3. The method for preparing a high-strength, high-thermal-conductivity micro / nano composite aramid insulating paper according to claim 1, characterized in that, The para-aramid fibers in step 1 have a diameter range of 8–12 nm and a length range of 4–10 μm; the meta-aramid chopped fibers in step 2 have a diameter range of 5–8 nm and a length range of 8–12 μm.

4. The method for preparing a high-strength, high-thermal-conductivity micro / nano composite aramid insulating paper according to claim 1, characterized in that, In step 1, the para-aramid fibers are first deprotonated and stripped; the alkaline buffer solution has a pH of 8.

5.

5. The method for preparing a high-strength, high-thermal-conductivity micro / nano composite aramid insulating paper according to claim 1, characterized in that, The stirring speed in step 2 is 800-1000 rpm.

6. The method for preparing a high-strength, high-thermal-conductivity micro / nano composite aramid insulating paper according to claim 1, characterized in that, In step 3, the core-shell slurry is washed, vacuum filtered and shaped to obtain a wet paper blank; the wet paper blank is then cold-pressed, dried and hot-pressed to obtain the desired composite aramid insulating paper.

7. The method for preparing a high-strength, high-thermal-conductivity micro / nano composite aramid insulating paper according to claim 6, characterized in that, The cold pressing process involves a pressure of 0.3–0.5 MPa and a pressing time of 4–6 min; the hot pressing temperature is 230–250 ℃, the pressure is 12–18 MPa, and the pressing time is 4–6 min.

8. The high-strength, high-thermal-conductivity micro / nano composite aramid insulating paper obtained by any one of the preparation methods described in claims 1 to 7, characterized in that, The composite aramid insulating paper is mainly composed of meta-aramid short-cut fibers, and the surface of the main body is covered with a thermally conductive shell network. The thermally conductive shell network includes para-aramid fibers and two-dimensional thermally conductive nanofillers. The surface of the para-aramid fibers is coated with polydopamine, and the two-dimensional thermally conductive nanofillers are anchored to the surface of the para-aramid fibers by polydopamine.

9. The high-strength, high-thermal-conductivity micro / nano composite aramid insulating paper according to claim 8, characterized in that, The composite aramid insulating paper has a thickness of 45–55 μm and a density of 0.75–0.85 g / cm³.

10. The application of the high-strength, high-thermal-conductivity micro / nano composite aramid insulating paper as described in any one of claims 8 to 9, characterized in that, The composite aramid insulating paper is used for insulating components of electronic devices.